An economic evaluation of pre-dialysis stage of chronic kidney disease - E. I. Rumiantseva; M. V. Avxentyeva (IRBIS LLC, 2021)
Objective: to review clinical and economic studies on the pre-dialysis stage of chronic kidney disease (CKD) and the cost-effectiveness of medical interventions used to detect CKD and prevent its progression.Material and methods. Articles were collected from the bibliographic databases PubMed, Cochrane Library and eLibrary for 2010-2020. Keywords for the search: 'chronic kidney disease (CKD)', 'cost-effectiveness', 'economic evaluation', 'economic burden', 'cost', 'healthcare'. After the selection and elimination of the repeated articles, we reviewed 36 Russian and foreign studies on the economic burden of CKD and the clinical and economic effectiveness of various medical interventions of the CKD pre-dialysis stage.Results. We found 21 studies on the economic burden of CKD. A significant part of them (n=6) was performed in the United States.The methodology for assessing the economic burden varied significantly from study to study. Studies on medical interventions at the CKD predialysis stage can be divided into three groups: Group 1 (n=9) - studies on the clinical and economic effectiveness of screening programs; Group 2 (n=3) - studies on the clinical and economic effectiveness of nephroprotectors and other drugs that slow down the course of CKD; and Group 3 (n=3) - studies on the clinical and economic effectiveness of multidisciplinary care. We concluded on the clinical and economic feasibility of most interventions that were used to detect CKD and prevent its progression.Conclusion. We did not find any scientific data that could currently serve as a justification for the clinical and economic feasibility of CKD control programs in the Russian Federation. At the same time, studies conducted in foreign countries on the screening for CKD and some interventions aimed at slowing the progression of CKD suggest that in the Russian Federation, such approaches can be justified not only clinically, but also economically. It is necessary to conduct domestic research on the clinical and economic feasibility of interventions aimed at identifying and treating CKD at an early stage.